Protein Recovery from Dairy Sludge by Fenton Process - Mehrdadi 1, Naser; Nabi Bidhendi 1, Gholamreza; Nazemi 2, Saeid; Roudbari 3, Aliakbar (Shahroud Journal of Medical Sciences, 2018)
Background: Holding excessive amount of sludge has turned into a major problem for the wastewater treatment plants. Nucleic acids, enzymes, proteins, and polysaccharides are some organic materials which could be found in the sludge. The main objective of this study was to investigate the efficiency of Fenton process in protein recovery from dairy sludge.Methods: Our case for the study was the waste activated sludge produced at the wastewater treatment plant of Fajr dairy industry in Shahrood, Iran. Fenton process was applied to a 1.5 L sludge sample. At first, the pH of the sludge was adjusted to 3 using H2SO4. The second step was the addition of Fe(II) at certain concentrations. Then, different H2O2 concentrations were added to the sample. The mixed sample was stirred at 120 rpm for 6 h and was neutralized with Ca(OH)2.The sludge was dewatered in the pilot-scale filter press and filtered. The soluble protein content in the supernatant of the disintegrated sludge derived from the Fenton process was recovered by dialysis and dried at −40°C for 24 h.Results: The results showed that after the Fenton process, SSi, TCODi, SCODi, and SCODa levels were 11275, 13800, 115, and 3450 mg/L respectively. Also, after the Fenton process, the concentration of the soluble proteins increased from 52.48 to 1732 mg/L, whereas after subsequent protein recovery, its concentration in the supernatant was 1180 mg/L.Conclusions: Based on the findings, the protein recovered from the excess sludge throughout the Fenton process can be used as animal feed.